2016
DOI: 10.2337/dc16-1194
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Neonatal Morbidity for Women Who Would Be Added to the Diagnosis of GDM Using IADPSG Criteria: A Secondary Analysis of the Hyperglycemia and Adverse Pregnancy Outcome Study

Abstract: OBJECTIVETo assess the frequency of adverse outcomes for women who are diagnosed with gestational diabetes mellitus (GDM) by the International Association of the Diabetes and Pregnancy Study Groups (IADPSG) criteria using data from the Hyperglycemia and Adverse Pregnancy Outcome (HAPO) study.RESEARCH DESIGN AND METHODSThis is a secondary analysis from the North American HAPO study centers. Glucose measurements from a 75-g oral glucose tolerance test were used to group participants into three nonoverlapping cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 19 publications
2
87
2
2
Order By: Relevance
“…In line with the reported figure for GDM, Sacks et al (29) found the overall frequency of GDM was 17.8% and ranged between 9.3 and 25.5% among centers that participated in HAPO Study using the IADPSG criteria and Waters et al (30) out of meta-analysis found 14.3% of studied pregnant women had GDM defined according to IADPSG criteria. Also, Lacaria et al (31) and Du et al (32) reported prevalence rates of GDM of 10.9% and 8.5%, respectively.…”
Section: Discussion:-mentioning
confidence: 65%
“…In line with the reported figure for GDM, Sacks et al (29) found the overall frequency of GDM was 17.8% and ranged between 9.3 and 25.5% among centers that participated in HAPO Study using the IADPSG criteria and Waters et al (30) out of meta-analysis found 14.3% of studied pregnant women had GDM defined according to IADPSG criteria. Also, Lacaria et al (31) and Du et al (32) reported prevalence rates of GDM of 10.9% and 8.5%, respectively.…”
Section: Discussion:-mentioning
confidence: 65%
“…Without preventive care almost half of women with gestational diabetes go on to develop type‐2 diabetes, and a significant proportion develop premature cardiovascular disease within 10 years of childbirth . Children born to women with HIP are also at very high risk of obesity, early onset type‐2 diabetes, and cardiovascular disease, whereby HIP perpetuates these conditions into the next generation.…”
Section: Disclosure Of Interestsmentioning
confidence: 99%
“…In 2013, an NIH consensus conference on diagnosing GDM was held to “address controversial questions of public health importance when there may be discordance between clinical practice and the available evidence.”[8] While there have been observational studies and a pilot feasibility trial comparing the two groups, [1214] there has yet to be a confirmatory, randomized controlled trial directly comparing the one-step (IADPSG) and two-step (CC) approaches. Thus, the consensus committee recommended continuing with the two-step approach until there is sufficient evidence from randomized trials on comparative detection, treatment, and outcomes.…”
Section: Introductionmentioning
confidence: 99%